Effect of Constant Magnetic Field on Convective Heat Transfer through Anisotropic River Beds - YOVOGAN, JULIEN; DEGAN, GÉRARD; FAGBEMI, LATIF ADÉNIYI (My University, 2018)
An analytical investigation is conducted to study the effect of magnetic field on convection heat transfer through packed porous beds which consists of a horizontal fluid layer (river bed) and a porous zone with anisotropic permea- bility and underlined by a surface heated by a constant temperature T1 . The free surface of the fluid layer overlying the horizontal porous layer receives solar rays to length of day and is then considered heated isothermally at tem- perature T 2 such as T 1 < T 2 . Flow in porous medium is assumed to be go- verned by the generalized Brinkman-extended Darcy law and in the fluid layer by the Navier-Stokes model. The Beavers-Joseph condition is applied at the interface between the two layers. The influence of Hartmann number and hy- drodynamic anisotropy on the convective phenomenon is investigated analyt- ically. It is found that the magnetic field, the anisotropic permeability and the thickness of the porous lining, ε , have a strong influence of the geothermal convective flow and the heat transfer rate.
Keywords: Hartmann Number; Hydrodynamic Anisotropy; Convection Heat Transfer